KOMPUTERISASI PENGELOLAAN ASET PADA SLBN 1 LINGGO SARI BAGANTI DENGAN SISTEM INFORMASI BERBASIS DESKTOP MENGGUNAKAN VISUAL BASIC 2010 DAN DIDUKUNG DATABASE MYSQL - Vratiwi, Septiana; Mayeni, Riska; A, Taufik Abdul Hasan; Putra, Dino Adi; H, Riski Randa (STKIP Pesisir Selatan, 2022)
Assets are one of the determining factors for a school to be advanced and of high quality. The more assets owned by a school show maturity in terms of facilities and infrastructure as well as development. Moreover, SLBN 1 Linggo Sari Baganti is the only Extraordinary School located in Linggo Sari Baganti District where every year it always receives assistance in many aspects. This is not comparable to the process of managing these assets which is still done manually through data collection that is still in the ledger. The purpose of this research is to design a computerized system to be able to carry out the procurement of goods, borrowing, returning, repairing goods to the procurement of consumables quickly and accurately. So that the results of this study are in the form of a system that can be utilized by asset management personnel at SLBN Linggo Sari Baganti to assist their activities so that they can be carried out effectively, quickly and precisely